Réplica a una crítica marxista del Principio de Diferencia de John Rawls - Morales, Jorge A. (2014)
This paper replies a marxist-inspired argument against the difference principle and against John Rawls’ theory of justice as a whole. The paper addresses the soundness of the arguments in terms of their consistency both as a marxist critique and as an internal critique of John Rawls’ Theory of Justice.